Maternal, fetal & neonatal physiology a clinical perspective - Blackburn, Susan Tucker (Elsevier Saunders, 2013)
Provide the best care possible with expert insight and clinically relevant coverage of the physiologic changes that occur throughout all major periods of the perinatal experience - prenatal, intrapartum, postpartum, and neonatal. Maternal, Fetal & Neonatal Physiology: A Clinical Perspective, 4th Edition gives you a solid foundation for assessment and therapeutic interventions, featuring an emphasis on the evolving interrelationships between mother, fetus, and neonate and adaptations of preterm and term infants to the extrauterine environment. Solid coverage of the physiologic bases for assessment and therapeutic interventions make this an ideal resource for advanced practice. Synthesis of the latest research studies and evidence-based practice provides vital data on normal physiologic changes during the antepartum, intrapartum and postpartum periods; anatomic and functional development of the fetus; and developmental physiology of preterm and term neonates.